1998
DOI: 10.2224/sbp.1998.26.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Life Demands in College Students

Abstract: Researchers have proposed that life satisfaction may be increased by reduced life involvement (i.e., the scarcity hypothesis) or increas ed by greater life involve ment (i.e., the expansion hypothesis). In this study we aimed to determine if female and male college students are more satisfied with their lives if they have more or less a ctive life styles. A total of 157 females and 86 males were assigned to either a high, moderate, or low life satisfaction group and additional instruments were administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
2
28
1
1
Order By: Relevance
“…Within this population, stress is a critical issue: most students (52 to 75%) report an intermediate or a high level of stress [1][2][3][4] which may impair health [2,[5][6][7][8]. Academic stress contributes to the deterioration of the students' quality of life and causes drug abuse and academic failure [4,[9][10][11][12][13][14].…”
Section: Résumémentioning
confidence: 99%
“…Within this population, stress is a critical issue: most students (52 to 75%) report an intermediate or a high level of stress [1][2][3][4] which may impair health [2,[5][6][7][8]. Academic stress contributes to the deterioration of the students' quality of life and causes drug abuse and academic failure [4,[9][10][11][12][13][14].…”
Section: Résumémentioning
confidence: 99%
“…Previous research has found that college stress levels were often associated with cognitive deficits (for example, attention and concentration difficulties), illness, increased rates of depression and anxiety, and decreased life satisfaction (Bailey and Miller 1998;Chang 2001;Dyson and Renk 2006;Edwards et al 2001;Lumley and Provenzano 2003;Pritchard et al 2007). Poor health behaviors were also linked with high levels of collegiate stress.…”
mentioning
confidence: 99%
“…In a study by Bailey and Miller (1998), it was proposed that students who were more satisfied with their lives also had more satisfying family relationships. In another study, Edward and Lopez (2006) reported that perceived family support was a significant predictor of life satisfaction.…”
mentioning
confidence: 99%